Digital Transformation and Service Performance: Managing Public Feedback Systems in Public Sector Organizations - I Made Panji Ananda Pahlawan; I Nyoman Subanda (Dinasti Research, 2026)
This study examines the mechanism of public aspiration delivery through the e-Audiensi system and its implications for public participation and legislative performance transparency at the Secretariat of the Regional House of Representatives of Bali Province. The study is motivated by the need to transform conventional aspiration channels, which were considered less efficient and less accessible, into a more effective and transparent digital system. This research employed a qualitative approach with a descriptive case study design. Data were collected through observation, in-depth interviews with internal and external informants, documentation, and literature review. The data were analyzed using qualitative techniques, including data reduction, data presentation, and conclusion drawing, supported by source and method triangulation. The findings reveal that the e-Audiensi system has improved the efficiency of administrative processes and expanded public participation by enabling online submission of aspirations. Compared to the conventional system, the mechanism is more structured, documented, and easier to manage. The number of aspirations submitted through e-Audiensi increased significantly in 2025, indicating growing public adaptation to the digital system. In terms of legislative performance, the system enhances accountability through digital documentation and follow-up actions. Responsiveness is also supported through notification features, although response times remain inconsistent. However, transparency is still limited because the system only covers submission, verification, and scheduling stages without providing real-time tracking or publication of hearing outcomes. Overall, the e-Audiensi system contributes positively to efficiency, effectiveness, and accountability, although further development is needed to strengthen transparency, responsiveness, and broader public accessibility.